2022
DOI: 10.1200/jco.21.02170
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancers Are Immunogenic: Immunologic Analyses and a Phase II Pilot Clinical Trial Using Mutation-Reactive Autologous Lymphocytes

Abstract: PURPOSE Metastatic breast cancer (mBrCa) is most often an incurable disease with only modest responses to available immunotherapies. This study investigates the immunogenicity of somatic mutations in breast cancer and explores the therapeutic efficacy in a pilot trial of mutation-reactive tumor-infiltrating lymphocytes (TILs) in patients with metastatic disease. PATIENTS AND METHODS Forty-two patients with mBrCa refractory to previous lines of treatment underwent surgical resection of a metastatic lesion(s), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
81
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 26 publications
0
81
0
Order By: Relevance
“…Zacharakis and colleagues reported that one patient with metastatic breast cancer who was treated with TILs reactive against the mutant versions of four proteins (SLC3A2, KIAA0368, CADPS2, and CTSB) in conjunction with IL-2 and the checkpoint blockade mediated the complete durable regression of metastatic breast cancer for >22 months, revealing a novel immunotherapy approach for the treatment of breast cancers ( 83 ). After the initial case report of treatment using TIL, Zacharakis and colleagues reported a preliminary result of a pilot trial of mutation-reactive TILs in patients with metastatic breast cancer ( 84 ). They were able to isolate and grow TILs in culture from the resected lesions of all 42 patients.…”
Section: Adoptive Cell Transfer–based Therapymentioning
confidence: 99%
“…Zacharakis and colleagues reported that one patient with metastatic breast cancer who was treated with TILs reactive against the mutant versions of four proteins (SLC3A2, KIAA0368, CADPS2, and CTSB) in conjunction with IL-2 and the checkpoint blockade mediated the complete durable regression of metastatic breast cancer for >22 months, revealing a novel immunotherapy approach for the treatment of breast cancers ( 83 ). After the initial case report of treatment using TIL, Zacharakis and colleagues reported a preliminary result of a pilot trial of mutation-reactive TILs in patients with metastatic breast cancer ( 84 ). They were able to isolate and grow TILs in culture from the resected lesions of all 42 patients.…”
Section: Adoptive Cell Transfer–based Therapymentioning
confidence: 99%
“…Nevertheless, all the combination approaches broadly weaken the TME either through the influence of cell dividing processes through chemotherapy or immunomodulation using CPIs. This is done either before or at the same time as the cellular therapy is administered [88][89][90][91][92][93][94][95][96]. However, chemotherapy and CPIs are administered systematically, which widens the side effect profile.…”
Section: Cellular Immunotherapymentioning
confidence: 99%
“…Another clinical trial in a metastatic breast cancer patient found that adoptive transfer of TILs reactive against neoepitopes derived from four proteins combined with interleukin-2 and ICB resulted in complete durable regression for over 22 months ( 53 ), implying clinical benefits of combining ACT with other immunomodulators such as the checkpoint inhibitor. At the same, after adoptive transfer of enriched neoantigen-specific TILs combined with anti-PD-1 antibody pembrolizumab in a phase II pilot trial, three of the six patients with metastatic breast cancer showed objective tumor regression, including one complete response that was ongoing for more than 5.5 years ( 54 ).…”
Section: Identification Of Immunogenic Neoantigensmentioning
confidence: 99%